Factors Related To The Occurrence Of Gastritis At Lubuk Pinang Heakth Center, Mukomuko Regency - Sepriwendi, Sepriwendi; Darmawansyah, Darmawansyah; Wulandari, Wulandari; Suyanto, Jipri; Habibi, Julius (Journal Hygeia Public Health, 2024)
Intoduction: Gastritis is a disease of the upper gastrointestinal tract characterized by severe pain in the upper abdomen. WHO data indicates that the number of gastritis cases reaches 1.8-2.1 million. The incidence of gastritis in Indonesia has a prevalence of 274,396 cases out of 238,452,952 residents. Data from the provincial health office records 1,620 cases, while data from Lubuk Pinang health center shows 64 cases. Many people have the habit of smoking, experience stress, and frequently consume Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). The aim of this study is to identify the factors related to the incidence of gastritis. Method: This research is a quantitative study using a cross-sectional design. The population consists of 582 individuals. The sampling technique used is accidental sampling. The analysis used is univariate analysis and bivariate analysis with the Chi-Square test.Result and Discussion: A small percentage of respondents experienced gastritis, the majority of respondents did not consume NSAIDs, most respondents did not smoke, and most respondents experienced mild stress. There is a relationship between NSAID consumption (p=0.006) and stress levels (p=0.000) with the incidence of gastritis. There is no relationship between smoking habits and the incidence of gastritis (p=0.577). Conclusion: The conclusion of this study is that gastritis is influenced by stress levels and NSAIDs, but there is no relationship with smoking habits.